Performance Of Piston Rod And Collar In Hydraulic Cylinder With Different Shapes And Material Configuration (Indo-American Journal of Life Sciences and Biotechnology, 2021)
There is an ever-increasing demand for increasingly powerful systems to implement theories as thedesign industry grows more serious. It is possible to move things using hydraulic cylinders, which aremechanical devices. It is imperative that the interior segments of the chamber be able to handle thegreater load placed on them in heavier applications where larger yield powers are required, and this iswhere the design of pressure-driven chamber inward segments comes into its own. Depending on thedesign, a screw or nut connects the cylinder rod and piston within the chamber. This research focusesprimarily on the joints that are subjected to greater tractable or compressive loads during dailyactivities. During execution action, the chamber responds and reaches an outlandishly empty state. It'spossible that a cylinder's joint and chamber will stop working altogether when there isn't any moreavailable stroke, which will result in a large ductile load on the bar and cylinder pole joints. Fourcompound chamber pole cylinder joints were subjected to a static structural analysis to examine thevarious workloads these joints can bear and which joint is best suited for modern applications with highmalleable loads.